Assessment of layout solutions for a service enterprise - Dashyvets, Halyna; Дашивець, Галина Іванівна (Запоріжжя : ТДАТУ, 2024)
EN: The most important condition for developing the material and technical base of society is the creation of modern enterprises based on advanced principles of production organization, with the broad introduction of comprehensive mechanization and automation of technological processes. During the design stage of technical service enterprises, tasks must be solved to optimize the sizes, capacities, layout solutions, and territorial placement of enterprises, improving labor productivity, and more. To align the service enterprise's subdivisions, select the optimal direction for the production process, internal transportation, and cargo and personnel flows, layout planning is carried out. Layout planning involves a schematic plan of the enterprise's building, showing production subdivisions, auxiliary, and utility-service rooms.
Keywords: cargo flow diagram; production building subdivisions; equipment types; calculations